Analisis Peran BPJS Ketenagakerjaan dalam Meningkatkan Kesejahteraan Sosial Pekerja Informal di Padang Bulan Kota Medan - Rajagukguk, Silvia N (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the role of BPJS Ketenagakerjaan in improving the social welfare of informal workers in the Padang Bulan area, Medan City. Informal workers are a group that is vulnerable to various work risks because they do not have a formal employment relationship, employment legal protection, or automatic access to social security. Through a qualitative approach, this study explores the experiences and perceptions of informal workers regarding their participation in the BPJS Ketenagakerjaan program. The results of the study indicate that BPJS Ketenagakerjaan plays an important role in providing a sense of financial and social security, especially through the Work Accident Insurance (JKK), Death Insurance (JKm), and Old Age Security (JHT) programs. However, the participation of informal workers is still relatively low due to various obstacles such as lack of understanding, distrust of the effectiveness of the program, complicated bureaucracy, and income instability. Therefore, a more participatory socialization strategy is needed as well as more inclusive and adaptive policies to expand the scope of social protection for workers in the informal sector.